2004
DOI: 10.1055/s-2004-821216
|View full text |Cite
|
Sign up to set email alerts
|

Prognostische Faktoren für den Erfolg einer intrauterinen Insemination: Eine Evaluation von 1005 Zyklen bei 349 Frauen

Abstract: Die intrauterine Insemination (IUI) stellt im Vergleich zur extrakorporalen Befruchtung eine sehr viel weniger invasive, weniger zeitintensive und nicht zuletzt kostengünstigere Methode der Sterilitätstherapie dar. Um den Stellenwert der IUI besser diskutieren zu können, wurde anhand von 1005 IUI-Zyklen bei 349 Frauen retrospektiv Prognosefaktoren analysiert. Bei 29,2 % der Patientinnen konnten mit einer Insemination eine Schwangerschaft erzielt werden. Die Schwangerschaftsrate pro Zyklus lag in den ersten 4 Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…After 3 cycles, couples in our cohort with a score of 5 had a cumulative probability of pregnancy of approximately 45%. In contrast, couples with a score of 0 only had a cumulative probability of 5% Our per cycle pregnancy rate agreed with previous studies, which reported rates between 7 and 15% [ 19 23 ]. However, our average per patient pregnancy rate was lower than the 29–43% reported by the same authors [ 21 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…After 3 cycles, couples in our cohort with a score of 5 had a cumulative probability of pregnancy of approximately 45%. In contrast, couples with a score of 0 only had a cumulative probability of 5% Our per cycle pregnancy rate agreed with previous studies, which reported rates between 7 and 15% [ 19 23 ]. However, our average per patient pregnancy rate was lower than the 29–43% reported by the same authors [ 21 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, couples with a score of 0 only had a cumulative probability of 5% Our per cycle pregnancy rate agreed with previous studies, which reported rates between 7 and 15% [ 19 23 ]. However, our average per patient pregnancy rate was lower than the 29–43% reported by the same authors [ 21 , 23 , 24 ]. This might have been due to a lower number of IUI cycles per couple in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data show that insemination therapy is still justified in patients aged 40 and 41. The data presented here confirm the results of many other studies [4][5][6][7], which have all described the impact of increasing age on the success of insemination. Among the group of patients below the age of 25, no further pregnancies occurred after 2 insemination cycles.…”
supporting
confidence: 90%
“…A total of 4246 insemination cycles in 1612 women were included in the analysis. The average number of IUI cycles per patient was 2.24 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In this patient cohort, 158 patients became pregnant more than once through insemination.…”
mentioning
confidence: 99%